IMPLEMENTASI KEPUTUSAN BUPATI TENTANG PEMBENTUKAN DESA WISATA DI KABUPATEN SERANG (STUDI DESA WISATA POTENSI BAHARI) - Rahmawati Allyreza; Rahmi Winangsih (Badan Perencanaan Pembangunan Daerah Provinsi Banten, 2023)
Village tourism is currently one of the alternative destinations for nature tourism. This is also the case with the Wargasara Tunda Island tourist village in Serang Regency. Wargasara Tunda Island tourist village was established by the Decree of the Regent of Serang in 2021. However, in its implementation, there are still several problems, namely limited accessibility constraints, low public understanding of tourist villages and hygiene problems at tourist attractions. This study aims to describe and analyze how the policy implementation is using Charles O Jones' policy implementation theory, namely organizational structure, interpretation and implementation. The research method used is qualitative with a case study approach. Data analysis according to Miles and Huberman with research informants determined by purposive informants. The results showed that the implementation of the policy on the establishment of Wargasara Tourism Village on Tunda Island has run optimally with some emphasis. From the organizational, institutional and human resource dimensions of the Tourism Village, it is good with the formation of Pokdarwis Jalatunda, which consists of village youth with tourism interests. The element of interpretation is interpreted variously by the village government who realizes that there are accessibility and electricity network constraints for more advanced tourism development, while from the community side, there is an increased understanding that the potential of the Wargasara area is a tourist destination. The dimension of policy implementation has not gone well where the application of Sapta Pesona has not gone well, especially cleanliness and beauty. Therefore, it is necessary to build synergistic collaboration between parties to overcome barriers to accessibility and electricity networks and increase public understanding of sustainable tourism so that tourism runs and the environment is maintained.